Intrinsic vs. extrinsic motivation: Which drives long-term employee productivity in hotels? - Bhaskar Sailesh; K Karthikeyan (Journal of Rural Tourism, 2026)
Purpose – This study aims to examine the influence of intrinsic and extrinsic motivation on long-term employee productivity in the luxury hospitality industry, with particular focus on organizational trust, psychological safety, and employee engagement as key determinants of workforce stability.Design/Methodology/Approach – The study adopts a conceptual and analytical approach by integrating established theoretical frameworks, including Self-Determination Theory, Kahn’s Engagement Model, and Job Demands-Resources Model. These models are used to evaluate how different motivational drivers shape employee engagement, performance, and retention in high-pressure hotel environments.Findings – The findings indicate that intrinsic motivation—such as autonomy, job satisfaction, and career development—has a stronger and more sustainable impact on long-term employee engagement and productivity. In contrast, extrinsic motivation, including salary, incentives, and promotions, tends to produce short-term performance improvements. The study also highlights the critical role of leadership, organizational trust, and open communication in fostering psychological safety, which enhances employee commitment and encourages service innovation. Cultural and organizational contexts are found to further influence motivational dynamics.Originality/Value – This study contributes to hospitality management literature by offering a comprehensive synthesis of motivation theories within the luxury hotel context. It provides practical recommendations for balancing financial and non-financial rewards, supporting human resource strategies aimed at reducing turnover, enhancing service quality, and strengthening long-term organizational performance.